An Analysis of the Dhuha Prayer Program in Shaping Religious Character among 5ÔÇô6-Year-Olds in Kindergarten - Qistina, Nur Izzah; Khadijah, Khadijah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Religious character development in early childhood is a fundamental aspect of moral and spiritual education, laying the groundwork for lifelong values and behavior. One effective approach to fostering religious character is through habituating acts of worship from an early age. This study aims to analyze the implementation of the dhuha prayer program in shaping the religious character of early childhood learners at kindergarten. A qualitative descriptive method was employed, utilizing data collection techniques such as in-depth interviews, observation, and document analysis. The research subjects included the principal, teachers, and students in group B at Al-Fikri Integrated Islamic Kindergarten. The object of this study was the process of implementing the dhuha prayer program as a medium for religious character formation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the dhuha prayer program is conducted regularly through a habituation and exemplary approach led by teachers. Children are trained to perform dhuha prayer in congregation, recite short prayers, and internalize the meaning of worship from an early age. The program positively influences the development of religious character, reflected in increased awareness of worship, discipline, and responsibility toward religious practices. Challenges encountered include varying levels of understanding among children and inconsistency in practice at home. Overall, the program is effective in instilling religious values in early childhood education.┬á┬á